Bioaccessibility of target essential elements and contaminants from Fucus spiralis - Francisco, João (2019)
Fucus spiralis is an edible brown seaweed (SW) found in the Portuguese Coast that is still undervalued and not very well studied. However, SW are known to be nutritious and healthy foods, in part, for their potential to supply mineral nutrients to the body. Nevertheless, with the increasing levels of pollution in the coastal areas, SW can also accumulate some contaminants. Therefore, to expand the knowledge about this marine resource, the contents of Mg, Mn, Co, I, Cd, Pb, As and Hg in fresh and freeze-dried Fucus spiralis were determined before and after in vitro human digestion simulation. Magnesium was the major element with 11.86 mg/g dry weigh (DW), but it must be highlighted that I in this SW presented concentration values of approximately 135 μg/g DW. Concerning contaminants, F. spiralis seems to have low levels of Cd, Pb, and Hg. The elements’ bioaccessibility was always high, ranging between 45.8% (I – Fresh SW) and 88.5% (Hg – FD SW). The freeze-drying process seemed to enhance element bioaccessibility.